A distinct element based two-stage-structural model for investigation of the development process and failure mechanism of strainburst. (February 2020) - Hu, Lihua; Su, Guoshao; Liang, Xin; Li, Yingchun; Yan, Liubin
Abstract: Devoted to investigate the development process and failure mechanism of strainburst that frequently encountered in deep engineering, a distinct element based two-stage-structural model (TSSM) is proposed in this study. Based on experimental results, TSSM considers the structural effect (i.e., the stress path and boundary condition) of strainburst and divides its failure process into pre-peak static stage and post-peak dynamic stage. A comprehensive calibration procedure and parametric study for TSSM are presented. Numerical results of TSSM indicate that: the development of strainburst is a process of initiation, propagation, coalescence, interaction, and localization of tensile and shear cracks, leading to a multiple zonal failure pattern; both the crack growth and cumulative damage processes of strainburst undergo stages of low-speed growth, accelerated growth with "curvature increasing", high-speed approximately linear growth, and jumping growth; this high-speed approximately linear growth feature can provide early warning information of strainburst; the released kinetic energy of strainburst accounts for a small proportion of the elastic energy released by the rock and the loading system, indicating that increasing energy consumption is an effective way to mitigate strainburst disaster.